Control of SUMO and Ubiquitin by ROS: signaling and disease implications - Stankovic-Valentin, Nicolas; Melchior, Frauke (Molecular aspects of medicine, 2018)
Reversible post-translational modifications (PTMs) ensure rapid signal transmission from sensors to effectors. Reversible modification of proteins by the small proteins Ubiquitin and SUMO are involved in virtually all cellular processes and can modify thousands of proteins. Ubiquitination or SUMOylation is the reversible attachment of these modifiers to lysine residues of a target via isopeptide bond formation. These modifications require ATP and an enzymatic cascade composed of three classes of proteins: E1 activating enzymes, E2 conjugating enzymes and E3 ligases. The reversibility of the modification is ensured by specific isopeptidases. E1 and E2 enzymes, some E3 ligases and most isopeptidases have catalytic cysteine residues, which make them potentially susceptible for oxidation. Indeed, an increasing number of examples reveal regulation of ubiquitination and SUMOylation by reactive oxygen species, both in the context of redox signaling and in severe oxidative stress. Importantly, ubiquitination and SUMOylation play essential roles in the regulation of ROS homeostasis, participating in the control of ROS production and clearance. In this review, we will discuss the interplay between ROS homeostasis, Ubiquitin and SUMO pathways and the implications for the oxidative stress response and cell signaling.